An Unanticipated Role for Survivin in Organ Transplant Damage. Issue 5 (14th April 2014) - Cassis, P.; Solini, S.; Azzollini, N.; Aiello, S.; Rocchetta, F.; Conti, S.; Novelli, R.; Gagliardini, E.; Mister, M.; Rapezzi, F.; Rapezzi, S.; Benigni, A.; et al.
Abstract : Ischemia/reperfusion (I/R) injury is a major determinant of graft survival in kidney transplantation. Survivin, an inhibitor of apoptosis that participates in the control of mitosis and cell cycle progression, has been implicated in renal protection and repair after I/R injury; however, no study has been performed in the transplant setting. We investigated the role of survivin in modulating posttransplant I/R injury in syngeneic and allogeneic kidney grafts, and studied whether protection from I/R injury impacted on the recipient immune system, on chronic allograft nephropathy and rejection. We used genetically engineered mice with survivin haploinsufficiency and WT mice in which survivin over‐expression was induced by gene‐delivery. Survivin haploinsufficiency in syngeneic grafts was associated with exuberant I/R tissue injury, which triggered inflammation eventually resulting in graft loss. Conversely, survivin over‐expression in the grafts minimized I/R injury and dysfunction in syngeneic grafts and in a clinically relevant fully MHC‐mismatched allogeneic combination. In the latter, survivin over‐expression translated into limited anti‐donor adaptive immune response and less long‐term allograft injury with protection from renal parenchymal damage. Our data support survivin over‐expression in the graft as a novel target for protocols aimed at limiting tissue damage at the time of transplant ultimately modulating the recipient immune system. Abstract : This article discloses a novel role for survivin that regulates the tissue response against ischemia/reperfusion injury in kidney transplants and limits cellular anti‐donor alloimmune responses.